Bax assembles into large ring‐like structures remodeling the mitochondrial outer membrane in apoptosis. (18th January 2016) - Große, Lena; Wurm, Christian A; Brüser, Christian; Neumann, Daniel; Jans, Daniel C; Jakobs, Stefan
Abstract: The Bcl‐2 family proteins Bax and Bak are essential for the execution of many apoptotic programs. During apoptosis, Bax translocates to the mitochondria and mediates the permeabilization of the outer membrane, thereby facilitating the release of pro‐apoptotic proteins. Yet the mechanistic details of the Bax‐induced membrane permeabilization have so far remained elusive. Here, we demonstrate that activated Bax molecules, besides forming large and compact clusters, also assemble, potentially with other proteins including Bak, into ring‐like structures in the mitochondrial outer membrane. STED nanoscopy indicates that the area enclosed by a Bax ring is devoid of mitochondrial outer membrane proteins such as Tom20, Tom22, and Sam50. This strongly supports the view that the Bax rings surround an opening required for mitochondrial outer membrane permeabilization (MOMP). Even though these Bax assemblies may be necessary for MOMP, we demonstrate that at least in Drp1 knockdown cells, these assemblies are not sufficient for full cytochrome c release. Together, our super‐resolution data provide direct evidence in support of large Bax‐delineated pores in the mitochondrial outer membrane as being crucial for Bax‐mediated MOMP in cells. Synopsis: STED nanoscopy shows that upon apoptosis induction Bax molecules form ring‐like structures in the mitochondrial outer membrane (MOM) surrounding areas devoid of membrane proteins. The findings suggest the formation of large Bax‐delineated pores during MOM permeabilization. Activated Bax molecules assemble into ring‐like structures of variable sizes. Bax‐rings are observed in several cell lines. In Drp1 knockdown cells, the Bax‐rings are not sufficient for full cytochrome c release. The areas delineated by the Bax‐rings are devoid of Tom20, Tom22, and Sam50. Abstract : STED nanoscopy shows that upon apoptosis induction Bax molecules form ring‐like structures in the mitochondrial outer membrane (MOM) surrounding areas devoid of membrane proteins. The findings suggest the formation of large Bax‐delineated pores during MOM permeabilization.